Feeding habits of Paralabrax nebulifer (Serranidae) during reproductive and non-reproductive seasons in an adjacent area to Magdalena Bay, Baja California Sur, Mexico - Ysla-Guzmán, Julio Alejandro; Moreno-Sánchez, Xchel Gabriel; Rosales-Velázquez, Martín Oscar; Carrasco-Chávez, Víctor; Ortíz-Galindo, José Luis (Revista de Biología Marina y Oceanografía, 2021)
The barred sand bass Paralabrax nebulifer is a commercially important fish off the west coast of Baja California Sur. To assess the diet of this species and variations as a function of sex and reproductive condition, 60 specimens were captured using traps during seven seasonal sampling trips from August 2016 to August 2018 in an adjacent area to Magdalena Bay, Baja California Sur, Mexico. The stomach contents of 50 specimens were obtained (23 males and 27 females). Sex was diagnosed by direct observation of the gonads. Based on the gonadosomatic index, hepatosomatic index, and histological analyses, the reproductive season of the barred sand bass was corroborated for August 2016, April, August, and September 2017, and August 2018, and the non-reproductive season was corroborated for November 2016 and March 2018. The Index of Relative Importance (IRI) was used to classify the main diet components, which comprised three fish species, seven crustacean species, and one mollusk species. According to the IRI, the South American pilchard Sardinops sagax and the red pelagic crab Pleuroncodes planipes were the prey that contributed the most (55%) to the barred sand bass diet. The ANOSIM showed that there were significant differences in the amount and type of prey consumed by sex; the SIMPER analysis revealed that the species contributing the most to differences between the sexes were S. sagax (16.58%), Euphylax dovii (15.95%), Stenocionops ovata (12%), and P. planipes (11.82%) for females. There were significant differences in the amount and type of prey consumed between types of reproductive season; the species contributing the most to differences between seasons were Anchoa spp. (27.76%), and P. planipes for non-reproductive season (22.67%), and S. sagax (11.08%) for reproductive season. The feeding strategy of the barred sand bass was that of a specialist carnivorous predator that fed mainly on the fish Sardinops sagax during the reproductive season, which supply the dietary nutritional requirements of the lipids HUFA (arachidonic acid, 20:4n-6; eicosapentaenoic acid, 20:5n-3; docosahexaenoic acid, 22:6n-3), nutrients required to achieve reproductive success.